POLITICAL TRAJECTORY AND MONARCH OF RAMESHWARAM ISLAND THROUGH THE AGE - G., Ramamoorthy`; J., Albaris (International Journal of Psychosocial Rehabilitation, 2020)
The Rishis exhorted Rama to build up a Linga and to venerate it in order to cleanse himself of the transgression of Brahmahatya submitted by killing Ravana. Rama fixed a favorable time and sent Hanuman to mount Kailas for drawing a muhurta. The plate states as follows: Having, with the aim of curbing the southern district, evacuated the race of Cholas, given their territory to his own dependents, and made the masters of incredible nations. The Lankan occupation of Ramanathapuram district lasted hardly seven or eight years, but it made its way into the folklore of the people. Many stories, some fantastic, are still current. He had numerous urban areas in his ownership, and his capital is said to have been Fatan, whereas indicated by him, there was an icon weighed down with gems. A record dated A.D. 1550 states that Vitthala Raja conceded the town of Tiruppachetti to the Brahmins of the town and requested for the discontinuance of the toll on the travelers, visiting LakshmanTheertha at Rameshwaram. Sethupathis demonstrated extraordinary enthusiasm for spreading and improving the name and acclaim of Rameshwaram by including the sanctuary structures and the method of ensuring the Rameshwaram pioneers. They indicated unique enthusiasm for proliferating the popularity of Rameshwaram sanctuary by the method of ensuring the Rameshwaram pilgrims, including the sanctuary structures, conceding grounds and endowments, giving solaces to the explorers, and belittling researchers and mutts. From days of yore, the pioneer course to Rameshwaram lay inside the Marava nation.